Uji Efektivitas Pestisida Nabati Ekstrak Daun Sirsak (Annona muricata) Terhadap Pengendalian Hama Kutu Daun (Aphis gossypii) - Rizky Tri Nanda Sopyan; Saiman Rosamsi (Biosfer : Jurnal Biologi dan Pendidikan Biologi, 2024)
Aphids (Aphis gossypii) are among the most significant pests that cause considerable damage to various types of plants, making it necessary to apply effective and environmentally friendly control methods. Botanical pesticides have emerged as a promising alternative due to their active metabolite compounds such as tannins, saponins, flavonoids, and acetogenins, which can inhibit pest growth without causing negative impacts on the environment or human health. This study aimed to evaluate the effectiveness of soursop (Annona muricata) leaf extract as a botanical pesticide in controlling aphid infestations. Extraction was carried out using 95% methanol as the solvent, with extract concentrations of 0%, 30%, 35%, 40%, 45%, and 50%. The tests were conducted by spraying the extract onto aphids placed in Petri dishes, with four sprays applied at four-hour intervals over a 24-hour period. Data were analyzed using a one-way ANOVA followed by a post hoc test using SPSS version 29.0. The results showed that soursop leaf extract effectively suppressed aphid populations, with the 45% and 50% concentrations achieving a 100% mortality rate. According to the Regulation of the Minister of Health of the Republic of Indonesia No. 50 of 2017, a pesticide is considered effective if it kills ≥80% of the target insects. Therefore, a 30% concentration is considered sufficient for community use to maintain ecological balance